A NEW INTERPRETATION OF NON-HUMAN CONSCIOUSNESS IN SCIENCE FICTION: THE CASE OF NEAL ASHER’S POLITY UNIVERSE. - Umarkulova Munira Zakhidjan kizi (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This study examines Neal Asher’s Polity universe as a groundbreaking intervention in science fiction’s representation of non-human intelligence. Analyzing artificial intelligences (Penny Royal, Polity AIs) and alien species (Prador, Jain, Atheter) through frameworks of posthumanism (Braidotti), cognitive estrangement (Suvin), and sympoiesis (Haraway), the paper demonstrates how Asher constructs intelligences that operate beyond anthropomorphic paradigms. The research reveals three key innovations: (1) AI consciousness rooted in nonhuman cognition (Hayles), (2) alien subjectivities embodying radical alterity (Hollinger), and (3) hybrid ontologies dissolving the organic/synthetic binary (Bakker). These narrative strategies offer vital conceptual tools for contemporary debates in AI ethics, astrobiology, and posthuman philosophy.